If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3xy + 1)(2xy + -3) = 0 Reorder the terms: (1 + 3xy)(2xy + -3) = 0 Reorder the terms: (1 + 3xy)(-3 + 2xy) = 0 Multiply (1 + 3xy) * (-3 + 2xy) (1(-3 + 2xy) + 3xy * (-3 + 2xy)) = 0 ((-3 * 1 + 2xy * 1) + 3xy * (-3 + 2xy)) = 0 ((-3 + 2xy) + 3xy * (-3 + 2xy)) = 0 (-3 + 2xy + (-3 * 3xy + 2xy * 3xy)) = 0 (-3 + 2xy + (-9xy + 6x2y2)) = 0 Combine like terms: 2xy + -9xy = -7xy (-3 + -7xy + 6x2y2) = 0 Solving -3 + -7xy + 6x2y2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -3xy)(3 + -2xy) = 0Subproblem 1
Set the factor '(-1 + -3xy)' equal to zero and attempt to solve: Simplifying -1 + -3xy = 0 Solving -1 + -3xy = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3xy = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3xy = 0 + 1 -3xy = 0 + 1 Combine like terms: 0 + 1 = 1 -3xy = 1 Divide each side by '-3y'. x = -0.3333333333y-1 Simplifying x = -0.3333333333y-1Subproblem 2
Set the factor '(3 + -2xy)' equal to zero and attempt to solve: Simplifying 3 + -2xy = 0 Solving 3 + -2xy = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2xy = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2xy = 0 + -3 -2xy = 0 + -3 Combine like terms: 0 + -3 = -3 -2xy = -3 Divide each side by '-2y'. x = 1.5y-1 Simplifying x = 1.5y-1Solution
x = {-0.3333333333y-1, 1.5y-1}
| 12-4x=-15+2x | | x^6=1296 | | 5y-8x=8x | | f(x)=x+4(2x+1)8x^2+4 | | 4-6(2x-3)+1=3+7(5-x) | | 2-8m=14-3+8m | | t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 | | f(x)=tan*3*x | | 6(x-3)-5=21x-4-10x |